2020
DOI: 10.1038/s41598-020-63832-9
|View full text |Cite
|
Sign up to set email alerts
|

Darier disease is associated with heart failure: a cross-sectional case-control and population based study

Abstract: Human data supporting a role for endoplasmic reticulum (eR) stress and calcium dyshomeostasis in heart disease is scarce. Darier disease (DD) is a hereditary skin disease caused by mutations in the ATP2A2 gene encoding the sarcoendoplasmic-reticulum Ca2 + ATPase isoform 2 (SERCA2), which causes calcium dyshomeostasis and eR stress. We hypothesized that DD patients would have an increased risk for common heart disease. We performed a cross-sectional case-control clinical study on 25 DD patients and 25 matched c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…ER stress has been associated with a variety of skin disease conditions in several studies. Chronic dermal ER stress, caused by Darier's disease and Ekpoma virus (EKV), triggers PERK-CHOP, which then activates the ER-mediated mitochondrial apoptosis pathway, allowing skin cells to die (46)(47)(48)(49)(50). Keratinization disorders and Keratosis linearis with Ichthyosis Congenita and Sclerosing Keratoderma syndrome (KLICK syndrome) are caused by ER stress that activates UPR signaling and promotes these disorders (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress has been associated with a variety of skin disease conditions in several studies. Chronic dermal ER stress, caused by Darier's disease and Ekpoma virus (EKV), triggers PERK-CHOP, which then activates the ER-mediated mitochondrial apoptosis pathway, allowing skin cells to die (46)(47)(48)(49)(50). Keratinization disorders and Keratosis linearis with Ichthyosis Congenita and Sclerosing Keratoderma syndrome (KLICK syndrome) are caused by ER stress that activates UPR signaling and promotes these disorders (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…This observation also strengthens the clinical evidence of the important role of SERCA2 in heart failure pathophysiology. 36 For example, even though patients with DD present with a normal clinical heart phenotype, they have a 59% higher chance of being diagnosed with heart failure compared to those without DD. 36 Interestingly, the loss of the ATPA2A allele by itself does not affect cardiac performance, however, the development of heart conditions may be worsened in patients with ATPA2A mutation.…”
Section: Dd and Diabetesmentioning
confidence: 99%
“…36 For example, even though patients with DD present with a normal clinical heart phenotype, they have a 59% higher chance of being diagnosed with heart failure compared to those without DD. 36 Interestingly, the loss of the ATPA2A allele by itself does not affect cardiac performance, however, the development of heart conditions may be worsened in patients with ATPA2A mutation. 37 It can be concluded that DD is a multisystem rare autosomal dominant disorder that occurs typically in the first or second decade of life, and goes beyond involving the skin.…”
Section: Dd and Diabetesmentioning
confidence: 99%
“…1 The cause is a gene that encodes the sarco/endoplasmic reticulom Ca2+ ATP ase type 2, which causes calcium dyshomeostasis and endoplasmic reticulum stress including intercellular adhesion. 2,3,4 Its incidence is 1 to 9 per 100,000 individuals. The disease usually begins before the third decade of life with a peak in puberty (11-15 years old) 5,6 ;due to sweating ,sebum exertion or change in bacterial flora.…”
Section: Introductionmentioning
confidence: 99%
“…8 Classis DD is characterized by malodor keratotic, warty crusted papules and plaques, which are usually located in seborrheic areas, variable nail changes, whitish oral macules and papules(oral cobblestoning),and palmoplanta puctate pits that typically worsen in summer. 2,4 Treatments for DD include:1-topical treatments such as:(retinoids, 5-fu, diclofenac, tacrolimus, tacalcitol, and steroids),2-oral treatments such as:(retinoids, cyclosporine, doxycycline, magnesium chloride, and naltrexone ),3-physical approach such as:[dermabrasion, electrosurgical excision, surgical excision, lasers (Co2,pulse dye, Erbium),and radiotherapy]. 9 Acral hemorrhagic DD is a rare subtype with hemorrhagic macules and vesicles in extremities.…”
Section: Introductionmentioning
confidence: 99%